(untitled) (Journal of Libya for geographical studies, 2024)
The research was interested in studying the change in the pattern of land use and its impact on the vegetation cover in the municipality of Sabratha during the period from 1985 AD to the year 2015 AD using remote sensing and geographic information systems techniques, as those changes that occurred on the different types of natural vegetation in this region were monitored. The research aims to clarify the change in land use and to know the reasons leading to the increase in the encroachment of some patterns of use over others. Classification of satellite visual images of varying dates and the production of maps that form a database for each use and the extent of its development. A number of results have been reached, the most important of which is that there is a significant decrease in the lands of natural vegetation cover, with an annual rate of approximately 1500 AH / year, in contrast there is a significant increase in the area of ​​land uses for purposes The most important of them are: agricultural, pastoral and urban expansion at rates that reached approximately 1000 AH/year for the first purpose, approximately 360 AH/year for the second purpose, and 300 AH/year for the third purpose. Civilian towards what the region is exposed to from the eradication of its vegetation cover.